An Address of the Global Financial Crises with Unconventional Monetary Policies - Naape, Baneng; Masoga, Marius (Journal of Economics and Behavioral Studies, 2020)
This study aims to assess the impact and spill over effects of the United States (US) Quantitative Easing (QE) to South Africa. Using an event-study analysis on daily data spanning from 25/11/2008 – 12/12/2012 for selected QE dates, the study finds that US Treasury bills fall by 106 basis points on average during QE1, rise by 9 basis points and 8 basis points during QE2 and QE3, respectively. For South Africa, government bonds fall by 61 basis points on average during QE1, 9 basis points during QE2 and 2 basis points during QE3. This leads to the conclusion that UMPs boost the economy in the short run but hurt the economy in the long run, especially those that are targeting inflation, when used extensively. The policymakers should concentrate on the whole financial system to measure the financial risk, and thus consistently strengthen macro prudential orientation.